PENGUKURAN TINGKAT KEPUASAN MAHASISWA TERHADAP PELAYANAN PENDIDIKAN DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN: Measurement of Student Satisfaction Level to Educational Services in Education And Training Faculty - Denok Trisusanti; Nunuk Suryanti (UIR Press, 2017)
This study aims to determine students' perceptions of educational services and studentexpectations of educational services and the level of student satisfaction on the quality ofeducation services in the Faculty of Teacher Training and Education Universitas Riau Riau.This research is a descriptive type research with a quantitative approach. Population used inthis research is all active student of Faculty of Teacher Training and Education of IslamicUniversity of Riau force 2012-2015, with amount of sample 99 responden. Sampling was usedincidental sampling technique with data collection method using questionnaire anddocumentation. Data analysis technique using descriptive analysis and SERQUAL modelanalysis. The result of this research is seen from the dimensions (reliability, responsiveness,assurance, empathy, and tangible) shows that: Student's perception toward education serviceat UIP FKIP is included in good category, student expectation to service education in FKIPUIR is categorized as very expecting and the level of student satisfaction on the quality ofeducation services in UIR FKIP included in the category of not satisfied